2020
DOI: 10.17221/49/2019-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of assessors in the Czech Republic to the consumption of house cricket Acheta domestica L. - A preliminary study

Abstract: Sensory acceptability of the consumption of whole baked house crickets by assessors in the Czech Republic was investigated. The main aim was to observe attitudes to eating edible insects before and after their tasting and to assess the extent of the effect of prejudices. Hedonic evaluation of the overall acceptability of edible insects was carried out under laboratory conditions by trained assessors. Of the 98 panellists, 68 were willing to evaluate the sample visually and then by tasting. They showed statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…Previous reviews have indicated that the concept of eating insects would likely be more appealing to younger people than older people ( 4 , 21 , 22 ). In contrast, the majority of studies (61.1%) in our review concluded that there was no link between age and Westerners' acceptance of edible insects ( 39 , 41 , 42 , 48 , 51 , 55 , 56 , 58 , 61 , 62 , 64 , 66 , 72 74 , 86 , 104 106 , 108 , 109 , 117 ). However, 36.1% of all studies that evaluated the effect of age on consumers' acceptance observed a negative effect of age ( 2 , 64 , 65 , 67 , 71 , 76 , 77 , 87 , 92 , 93 , 97 , 99 , 115 ), which means that younger people had a higher acceptance of insect-based foods than older people, while two studies (5.6%) identified a positive connection ( 49 , 107 ).…”
Section: Resultscontrasting
confidence: 64%
See 3 more Smart Citations
“…Previous reviews have indicated that the concept of eating insects would likely be more appealing to younger people than older people ( 4 , 21 , 22 ). In contrast, the majority of studies (61.1%) in our review concluded that there was no link between age and Westerners' acceptance of edible insects ( 39 , 41 , 42 , 48 , 51 , 55 , 56 , 58 , 61 , 62 , 64 , 66 , 72 74 , 86 , 104 106 , 108 , 109 , 117 ). However, 36.1% of all studies that evaluated the effect of age on consumers' acceptance observed a negative effect of age ( 2 , 64 , 65 , 67 , 71 , 76 , 77 , 87 , 92 , 93 , 97 , 99 , 115 ), which means that younger people had a higher acceptance of insect-based foods than older people, while two studies (5.6%) identified a positive connection ( 49 , 107 ).…”
Section: Resultscontrasting
confidence: 64%
“…One of the most obvious and promising influences on the acceptance of insects as food in Western societies is previous insect consumption. Twenty-eight studies in our review inquired about their participants' experience with edible insects, and all of these studies, without exception, confirmed a positive impact of previous insect consumption on consumer acceptance of edible insects ( 36 , 37 , 50 , 59 , 61 , 64 , 66 , 70 , 73 , 77 , 78 , 86 , 87 , 92 , 94 , 99 , 104 106 , 108 , 109 , 112 , 113 , 117 , 143 , 144 ).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Non-traditional commodities can also be used to enrich bakery products such as edible insects [ 8 ]. Edible insects are foods that are consumed mainly in Asia, Africa, and Latin America [ 9 ]. In European countries, for example, in Italy or in France, Casu Marzu cheese [ 10 ] consists of proteins, minerals, and n-3 and n-6 fatty acids.…”
Section: Introductionmentioning
confidence: 99%